(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
In adult patients, the main issues of surgical tactics for large and giant incision hernias are discussed. As a result of the analysis of the causes of hernia recurrence, the reasons for the development of postoperative complications, the need for an algorithmic approach to the choice of the method of plasticizing the anterior abdominal wall, the criteria for the possibility of performing surgery were determined. assistance to patients with severe concomitant pathology, as well as a preoperative preparation program, was identified.